Architecture and art of southern India : Vijayanagara and the successor states, 1350-1750 - Michell, George (The new Cambridge history of India, 1995)
George Michell provides a pioneering and richly illustrated introduction to the architecture, sculpture and painting of Southern India under the Vijayanagara empire and the states that succeeded it. This period, encompassing some four hundred years, from the fourteenth to the eighteenth century, was endowed with an abundance of religious and royal monuments which remain as testimonies to the history and ideology behind their evolution.